THERMODYNAMIC INTERACTIONS OF 5-DECYLOXY-2-[[[4HEXYLOXYPHENYL]IMINO]METHYL] PHENOL WITH VARIOUS SOLVENTS - Yazici, Oezlem; Cakar, Fatih; Cankurtaran, Oezlem; Karaman, Belkis Bilgin Eran Ferdane (YILDIZ TECHNICAL UNIV, 2009)
In this study, thermodynamic interactions of 5-decyloxy-2-[[[4-hexyloxyphenyl]imino]methyl] phenol with octane, nonane, decane, ethyl acetate, isobutyl acetate and butyl acetate were examined by inverse gas chromatography method. Firstly, the specific retention volumes of the solvents were determined and the retention diagrams were plotted for liquid crystal-solvent systems. And then, the weight fraction activity coefficient, Flory-Huggins and equation of state interaction parameters, effective exchange energy parameter, exchange enthalpy and entropy parameters were calculated at the temperatures between 130 and 150 degrees C because thermodynamical equilibrium occurred at this temperature range.
Keywords: Inverse gas chromatography; interaction parameter; thermodynamics; liquid crystals; Engineering